AUTOMATIC FISH SORTER WITH MICROCONTROLLER BASED SUGENO FUZZY LOGIC - Rakhmat Kurniawan R; Muhammad Siddik Hasibuan; Ivan Prayuda (Sean Institute, 2022)
Sorting is a stage carried out by fish farmers during the harvesting process. So it is a tool that can help farmers do sorting during the harvest process. Automatic fish sorting tool with Sugeno Fuzzy logic based on a microcontroller is one solution to assist farmers in sorting. With this system we can reduce errors that often occur in the manual sorting process. The main cause of the manual sorting process is that many fish do not match market needs. This system is only used for the process of harvesting catfish for consumption. There are three classifications of weight categories on these tools including small, adequate and large, in the range of values ​​0-120g, moderately in the range of values ​​of 121-200g and large in the range of values ​​of 201-1000g. This study uses the Sugeno Fuzzy logic method because this method is suitable for use in most real-time problems such as making decisions to find things that are volatile and less certain. In this system there is a microcontroller that has been implanted with Sugeno Fuzzy logic. The sorting process is carried out using a Load Cell sensor as a fish weight counter and assisted by servo movement and the sorting results will be displayed on a 4x20 LCD.